Three-peak evolution characteristics of supporting stress on a super-long working face in a thick coal seam - Wang, Hongbing; Cheng, Zhiheng; Zhang, Jinhu; Chen, Liang; Luo, Xin; Li, Meichen; Chen, Haoyi; Xie, Yifei (Frontiers in Energy Research, 2023)
Increasing working face length is the development trend of intelligent and efficient longwall fully mechanized mining. By combining field measurement and theoretical calculation, change characteristics of the frequency, peak value, and range of weighting in a long working face in a 1000 m-deep shaft of Kouzidong Coal Mine (Fuyang City, Anhui Province, China) were studied. Based on the mechanical model of the hydraulic support group of the elastic independent support, force characteristics and posture change characteristics of the support in the 121304 working face of the mine were studied and analyzed. The supporting stress characteristics of the deep super-long working face were revealed, and the theoretical calculation was in good agreement with the actual measurement. Based on the aforementioned model, support parameters and control technology of the 140502 working face were studied. The results show that as the length of the working face increases, the supporting stress gradually transforms from a single peak to multiple peaks and expands to both ends of the working face. The weighting in different areas of the working face is characterized by an obvious time sequence and great difference in intensity. When the working face length is 300 m, the multi-peak characteristic of super-long working faces appears. The M-shaped three-peak characteristic can be used as the criterion for super-long working faces. A reasonable working face length should be determined by comprehensively considering occurrence conditions of coal seams, working face parameter, and equipment ability. According to the different attributes of hydraulic supports in space and function and combining with zonal characteristics of the long working face, the criterion for the super-long working face and the principle of zonal cooperative control of hydraulic support groups were revealed. In addition, a cooperative control method of equipment groups in the working face based on the state error and cost functions was put forward, and the three-level cooperative control strategy and implementation method were formulated. It can effectively guide the equipment group in the super-long fully mechanized working face in deep thick coal seams to achieve optimal coordinated control.